Modern inequalities generated by new forms of financial service delivery - Teixeira, Maria Emília (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The FinTech phenomenon has revolutionised the way financial services are provided and transformed the relationship between the provider of these services and the consumer, with digital platforms and apps being the means through which the consumer has come to relate to his or her financial services provider. The banking sector needs to adapt quickly and urgently to the new reality. The profile of the financial services consumer has changed and the more digital and technological the financial services providers become; new social inequalities arise. We propose to analyse which inequalities have been generated and what the current social impacts are.